Process for preparing battery-grade iron phosphate and lithium iron phosphate by utilizing recycled iron phosphorus slag
Battery-grade iron phosphate is prepared by recycling iron phosphorus slag, and iron phosphate is separated and purified by acid leaching and alkali treatment. The problem of iron phosphorus slag utilization and titanium doping affect performance is solved, and efficient recovery and high-performance lithium iron phosphate production are achieved.
Patent Information
- Application Number
- CN202411991296.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively utilize the iron-phosphorus slag after lithium extraction, resulting in waste of resources and environmental pollution. At the same time, titanium elements are needed to be doped when synthesizing lithium iron phosphate, which affects its performance.
Battery-grade iron phosphate is prepared by recycling iron-phosphorus slag, and iron phosphate is gradually separated and purified by acid leaching and alkali treatment, avoiding the step of doping titanium elements, thereby improving the performance of lithium iron phosphate.
Efficient recycling and utilization of iron-phosphorus slag is achieved, resource waste and environmental pollution are avoided. At the same time, due to the entry of titanium into the iron phosphate lattice, higher-performance lithium iron phosphate is obtained.
Smart Images

Figure CN119528099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of processing recycled iron-phosphorus slag, and specifically to a process for preparing battery-grade iron phosphate and lithium iron phosphate by utilizing recycled iron-phosphorus slag. Background Art
[0002] Lithium iron phosphate is a widely used cathode material for lithium-ion batteries, with the advantages of high specific capacity, high safety, and low cost. With the development of new energy vehicles and energy storage equipment, the demand for lithium iron phosphate batteries continues to increase, and a large number of waste lithium iron phosphate batteries are also generated. Waste lithium iron phosphate batteries contain not only high-value lithium elements, but also iron, phosphorus and other elements. If they are not recycled reasonably, it will cause resource waste and environmental pollution.
[0003] At present, the main methods for recovering lithium from waste lithium iron phosphate batteries include hydrothermal method, acid leaching method, alkaline leaching method, etc. These methods can effectively extract lithium from the positive electrode material, but there is no better way to utilize the iron-phosphorus slag after lithium extraction. Iron-phosphorus slag contains high levels of iron and phosphorus elements. If it is directly discharged or landfilled, it will occupy land resources and pollute soil and water quality. Therefore, how to recover and prepare battery-grade iron phosphate from iron-phosphorus slag after lithium extraction is an urgent problem to be solved.
[0004] On the other hand, the method of synthesizing lithium iron phosphate from iron phosphate is mainly carbon thermal reduction method, which usually requires doping titanium in iron phosphate to improve the conductivity and cycle stability of lithium iron phosphate. At present, titanium is mainly doped in the synthesis of lithium iron phosphate, and the uniformity of titanium is affected to a certain extent. Whether doping titanium in the synthesis of iron phosphate can better improve the performance of lithium iron phosphate is a question worth studying.
[0005] The prior art recovers the high-priced element lithium from the positive electrode material of the battery, but does not make good use of the high-content iron and phosphorus elements. The present invention proposes a method for producing battery-grade iron phosphate from iron-phosphorus slag after lithium extraction.
[0006] In the prior art, lithium iron phosphate is synthesized from iron phosphate, which generally requires doping with titanium. The iron phosphate prepared from recycled iron-phosphorus slag in the present invention contains titanium, so the step of doping with titanium can be omitted in the synthesis process of lithium iron phosphate, while obtaining lithium iron phosphate with higher performance. Summary of the invention
[0007] In view of the above problems, the present invention provides a process for preparing battery-grade iron phosphate and lithium iron phosphate using recycled iron-phosphorus slag. The prepared titanium-containing anhydrous iron phosphate contains an appropriate amount of impurity element titanium, so that the lithium iron phosphate can be synthesized without doping with titanium. At the same time, because titanium enters the iron phosphate lattice, higher performance lithium iron phosphate is obtained.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag comprises the following steps:
[0010] (1) The iron-phosphorus slag raw material is subjected to a first acid leaching and dissolution with sulfuric acid of 5-10% by mass, and the raw material mass is dissolved by 50-80%, and the primary leaching solution and primary leaching residue are obtained by filtration. The primary leaching residue is subjected to a second acid leaching with sulfuric acid of 11-50% by mass to completely dissolve the iron phosphate therein, and the secondary leaching solution and secondary leaching residue are obtained after filtration, and the secondary leaching residue is carbon black; new iron-phosphorus slag raw material is added to the secondary leaching solution, and an appropriate amount of low-concentration sulfuric acid is added to the acid leaching solution until the sulfuric acid concentration of the acid leaching solution is 5-10%, and a new primary leaching solution and primary leaching residue are obtained; the chemical reaction equation involved in the above acid leaching is as follows:
[0011] 2AlPO 4 +3H 2 SO 4 =Al 2 (SO 4 ) 3 +2H 3 PO 4
[0012] 2FePO 4 +3H 2 SO 4 =Fe 2 (SO 4 ) 3 +2H 3 PO 4
[0013] Ti 3 (PO 4 ) 4 +6H 2 SO 4 =3Ti(SO 4 ) 2 +4H 3 PO 4 ;
[0014] (2) Alkali is gradually added to the new primary leaching solution, and the end point pH value is controlled at 1-1.8. After filtering and washing, filter cake 1 and tail liquid are obtained. The chemical reaction equation involved in adjusting the pH value is as follows:
[0015] H 3 PO 4 +3OH - =PO 4 3- +3H 2 O
[0016] Fe3+ +PO 4 3- +2H 2 O=FePO 4 ·2H 2 O↓
[0017] 3Ti 4+ +4PO 4 3- =Ti 3 (PO 4 ) 4 ↓;
[0018] (3) After the filter cake 1 is dissolved with sulfuric acid, alkali is gradually added again by controlling the speed of adding alkali, and the end point pH value is controlled at
[0019] 1-1.8, filtering and washing to obtain filter cake 2;
[0020] (4) slurrying the filter cake 2 obtained in step (3) with pure water, adding phosphoric acid, adjusting the temperature to 85-95° C., keeping the temperature for 2 h, filtering to obtain the filter cake 3, and washing with pure water until the conductivity is less than 500 μS / cm;
[0021] (5) Drying and calcining the filter cake 3 obtained in step (4) to obtain anhydrous titanium-containing iron phosphate.
[0022] As a further improvement of the above scheme, in step (1), the temperature of the first acid leaching is 25-60°C; the temperature of the second acid leaching is 25-80°C, the amount of sulfuric acid added in the first acid leaching accounts for 50-80% of the total amount of sulfuric acid in the two acid leachings, and the amount of sulfuric acid added in the second acid leaching accounts for 20-50% of the total amount of sulfuric acid in the two acid leachings.
[0023] As a further improvement of the above scheme, the tail liquid in step (2) is treated by recycling and utilizing to prepare lithium carbonate. The specific recycling method is as follows: if the tail liquid is obtained after adding ammonia water to the new primary leachate to precipitate iron phosphate, then continue to add ammonia water to adjust the pH value to 5-6, filter to obtain a lithium-containing ammonium sulfate solution, and then perform MVR evaporation concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized ammonium sulfate to obtain a saturated ammonium sulfate mother liquor with a pH value of 2-3 and a lithium content of 1000-10000ppm, then add ammonia water or ammonium bicarbonate to adjust the pH to 5-7.5, filter to obtain calcium slag and magnesium slag, add ammonium bicarbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, and add ammonia water to adjust the pH value to 7.5-10, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, and wash with water Remove ammonium sulfate from lithium carbonate to obtain industrial-grade lithium carbonate wet cake, which is then dried to obtain industrial-grade lithium carbonate. Another method is to continue adding liquid alkali or sodium carbonate to adjust the pH value to 6-7 in the new primary leachate to obtain the tail liquid, and then filter to obtain a sodium sulfate solution containing lithium, and then perform MVR evaporation and concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized sodium sulfate to obtain a saturated sodium sulfate mother liquor with a pH value of 6-7 and a lithium content of 1000-10000ppm, then add sodium carbonate to adjust the pH to 6-7.5, filter to obtain calcium slag and magnesium slag, add sodium carbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, wash with water to remove sodium carbonate in the lithium carbonate, obtain an industrial-grade lithium carbonate wet cake, and dry to obtain industrial-grade lithium carbonate.
[0024] As a further improvement of the above scheme, the alkali in step (2) and step (3) is selected from liquid alkali or aqueous ammonia, the concentration of the liquid alkali is 10-30%, and the concentration of the aqueous ammonia is 5-20%.
[0025] As a further improvement of the above scheme, acidic water is used for washing in step (2) and step (3), and the pH value of the acidic water is 1-1.5.
[0026] As a further improvement of the above scheme, in step (4), the concentration of phosphoric acid is 75-85%, and the pH value is controlled at 0.8-2.0.
[0027] As a further improvement of the above scheme, in step (5), the drying temperature is 75-105°C, the drying time is 2-10h, and the calcination temperature is 500-600°C, and the time is 3-5h.
[0028] A process for preparing lithium iron phosphate by recycling iron phosphorus slag, wherein the iron phosphate prepared by the above process is mixed with lithium carbonate and glucose in a stoichiometric ratio, mixed evenly, and then wet-milled, dried, high-temperature sintered and ground to obtain lithium iron phosphate.
[0029] As a further improvement of the above scheme, the molar ratio of iron phosphate to lithium carbonate is 2-3:1, and the amount of glucose added accounts for 6-8% of the mass of the raw material mixture; the drying temperature is 95-105°C, the time is 3-5h, and the high-temperature sintering temperature is 700-750°C, and the time is 9-10h.
[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) the titanium-containing anhydrous iron phosphate prepared by the present invention contains an appropriate amount of impurity element titanium, so that there is no need to dope titanium in the process of synthesizing lithium iron phosphate. At the same time, because titanium enters the iron phosphate lattice, lithium iron phosphate with higher performance is obtained;
[0031] (2) The first acid leaching of the present invention only dissolves part of the iron phosphate in the iron-phosphorus slag, and the second addition of sulfuric acid with a relatively high concentration is to completely dissolve the iron phosphate, convert the strong acid sulfuric acid into weak acid phosphoric acid, and then the third acid leaching process is used to continue to use the acid contained in the new iron-phosphorus slag raw material to obtain an iron-phosphorus liquid with a lower acidity;
[0032] (3) The iron-phosphorus slag raw material used in the present invention is the slag after lithium extraction from the positive electrode material of the battery, and its lithium content is very low. When it is recovered alone, the energy consumed by evaporation and concentration is high and economically uneconomical. However, if lithium carbonate is recovered from the tail liquid of iron phosphate extracted from the iron-phosphorus slag, it is technically feasible and has economic value. The recovery process used can also fully convert lithium into lithium carbonate for recycling in a solution containing less lithium;
[0033] (3) In the present invention, in step (2), the iron-phosphorus liquid is subjected to secondary precipitation by controlling the rate of adding alkali and the end point pH value to achieve iron-aluminum separation in the iron-phosphorus liquid, and in step (3), alkali is continued to be added to control the pH value to continue the iron-aluminum separation; in step (4), the slurry is reacted with phosphoric acid to further remove impurities and convert it into dihydrated iron phosphate, and this step is an aging reaction; the drying is to remove the free water adsorbed by the dihydrated iron phosphate, and the calcination is to remove the crystallization water. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0036] In order to control the titanium content, this embodiment selects a raw material with a suitable titanium content, namely, the slag (iron-phosphorus slag) after lithium extraction from the positive electrode material of the battery.
[0037] In the following embodiments, the tail liquid is treated by recycling and preparing lithium carbonate. There are two specific recycling methods: one is that if the tail liquid is obtained after adding ammonia water to the new primary leachate to precipitate iron phosphate, then continue to add ammonia water to adjust the pH value to 5-6, filter to obtain a lithium-containing ammonium sulfate solution, and then perform MVR evaporation and concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized ammonium sulfate to obtain a saturated ammonium sulfate mother liquor with a pH value of 2-3 and a lithium content of 1000-10000ppm, then add ammonia water or ammonium bicarbonate to adjust the pH to 5-7.5, filter to obtain calcium slag and magnesium slag, add ammonium bicarbonate to the filtrate, the amount added is more than 1 times the molar number of lithium element in the solution, and add ammonia water to adjust the pH value to 7.5-10, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, and wash with water to remove the lithium carbonate. Ammonium sulfate is added to obtain industrial-grade lithium carbonate wet cake, which is then dried to obtain industrial-grade lithium carbonate. Another method is to add liquid alkali to the new primary leachate to precipitate iron phosphate to obtain the tail liquid, then continue to add liquid alkali or sodium carbonate to adjust the pH value to 6-7, filter to obtain a sodium sulfate solution containing lithium, and then perform MVR evaporation and concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized sodium sulfate to obtain a saturated sodium sulfate mother liquor with a pH value of 6-7 and a lithium content of 1000-10000ppm, then add sodium carbonate to adjust the pH to 6-7.5, filter to obtain calcium slag and magnesium slag, add sodium carbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, wash with water to remove the sodium carbonate in the lithium carbonate, obtain an industrial-grade lithium carbonate wet cake, and dry to obtain industrial-grade lithium carbonate.
[0038] Embodiment 1:
[0039] A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag comprises the following steps:
[0040] (1) The iron-phosphorus slag raw material is subjected to a first acid leaching dissolution with 5% sulfuric acid, and the raw material mass is dissolved by 50%. The primary leaching solution and the primary leaching residue are obtained by filtration. The primary leaching residue is subjected to a second acid leaching with 40% sulfuric acid to completely dissolve the raw material. After filtration, a secondary leaching solution and a secondary leaching residue are obtained, and the secondary leaching residue is carbon black; a new iron-phosphorus slag raw material is added to the secondary leaching solution and an appropriate amount of low-concentration sulfuric acid is added to the acid leaching solution until the sulfuric acid concentration of the acid leaching solution is 5%, and a new primary leaching solution and a primary leaching residue are obtained; the first acid leaching temperature is 60° C.; the second acid leaching temperature is 35° C., the amount of sulfuric acid added in the first acid leaching accounts for 50% of the total amount of sulfuric acid in the two acid leachings, and the amount of sulfuric acid added in the second acid leaching accounts for 50% of the total amount of sulfuric acid in the two acid leachings; the main chemical components in the above-mentioned new primary leaching solution are shown in the following table:
[0041] Table 1
[0042]
[0043] (2) Liquid alkali was gradually added to the new primary leaching solution at a controlled rate, with a concentration of 15% and an end point pH value of 1. After filtration and washing, filter cake 1 and tail liquid were obtained. The main chemical components of the filter cake 1 are shown in the following table:
[0044] Table 2
[0045]
[0046] (3) After dissolving the filter cake 1 with an appropriate amount of sulfuric acid, liquid alkali is gradually added again by controlling the speed of adding alkali, with a concentration of 20% and an end point pH value controlled at 1. The filter cake 2 is obtained by filtering and washing. The main chemical components of the filter cake 2 are shown in the following table; acidic water is used for washing in the steps (2) and (3), and the pH value of the acidic water is 1;
[0047] Table 3
[0048]
[0049] (4) slurrying the filter cake 2 obtained in step (3) with pure water, adding phosphoric acid, adjusting the temperature to 95° C., keeping the temperature for 2 h, filtering to obtain the filter cake 3, washing with pure water until the conductivity is less than 500 μS / cm, the phosphoric acid concentration is 75%, and the pH value is controlled at 0.9;
[0050] (5) drying and calcining the filter cake 3 obtained in step (4) to obtain anhydrous titanium-containing iron phosphate, the drying temperature is 75° C., the drying time is 10 h, and the calcination temperature is 500° C., and the time is 5 h;
[0051] The tail liquid in the above step (2) is treated in a manner of recycling and utilizing to prepare lithium carbonate. The specific recycling method is: adding liquid alkali to the tail liquid in step (2) to adjust the pH value to 6-7, filtering to obtain a sodium sulfate solution containing lithium, and then performing MVR evaporation concentration at a concentration temperature of 100° C., centrifuging and separating the crystallized sodium sulfate to obtain a saturated sodium sulfate mother liquor with a pH value of 6-7 and a lithium content of 1000-3000 ppm, then adding sodium carbonate to adjust the pH to 6-7.5, filtering to obtain calcium slag and magnesium slag, adding sodium carbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, and adding ammonia water to adjust the pH value to 7.5-10, stirring at a temperature of 80° C. for 2 hours, then keeping the temperature and standing for 15 hours, filtering to obtain a lithium carbonate filter cake, washing with water to remove sodium carbonate in the lithium carbonate to obtain an industrial-grade lithium carbonate wet cake, and drying to obtain industrial-grade lithium carbonate.
[0052] Embodiment 2:
[0053] A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag comprises the following steps:
[0054] (1) the iron-phosphorus slag raw material is subjected to a first acid leaching dissolution with 10% sulfuric acid, and the raw material mass is dissolved by 80%, and a primary leaching solution and a primary leaching residue are obtained by filtration. The primary leaching residue is subjected to a second acid leaching with 11% sulfuric acid to completely dissolve the raw material, and a secondary leaching solution and a secondary leaching residue are obtained after filtration. The secondary leaching residue is carbon black; new iron-phosphorus slag raw material is added to the secondary leaching solution and an appropriate amount of low-concentration sulfuric acid is added to the acid leaching solution until the sulfuric acid concentration of the acid leaching solution is 10%, and a new primary leaching solution and a primary leaching residue are obtained; the first acid leaching temperature is 25° C.; the second acid leaching temperature is 80° C., the amount of sulfuric acid added in the first acid leaching accounts for 80% of the total amount of sulfuric acid in the two acid leachings, and the amount of sulfuric acid added in the second acid leaching accounts for 20% of the total amount of sulfuric acid in the two acid leachings;
[0055] (2) In the new primary leaching solution, ammonia water is gradually added at a controlled rate of adding alkali, with a concentration of 18% and an end point pH value controlled at 1.1. After filtering and washing, filter cake 1 and tail liquid are obtained.
[0056] (3) After dissolving the filter cake 1 with an appropriate amount of sulfuric acid, ammonia water is gradually added again by controlling the speed of adding alkali, the concentration is 20%, and the end point pH value is controlled at 1.5, and the filter cake 2 is obtained by filtering and washing; acidic water is used for washing in the steps (2) and (3), and the pH value of the acidic water is 1.5;
[0057] (4) slurrying the filter cake 2 obtained in step (3) with pure water, adding phosphoric acid, adjusting the temperature to 85° C., keeping the temperature for 2 h, filtering to obtain the filter cake 3, washing with pure water until the conductivity is less than 500 μS / cm, the phosphoric acid concentration is 85%, and the pH value is controlled at 1.2;
[0058] (5) drying and calcining the filter cake 3 obtained in step (4) to obtain anhydrous titanium-containing iron phosphate, the drying temperature is 105° C., the drying time is 2 h, and the calcination temperature is 600° C., and the time is 3 h;
[0059] The tail liquid in the above step (2) is treated in a manner of recycling and utilizing to prepare lithium carbonate. The specific recycling method is: continue to add ammonia water to the tail liquid in step (2) to adjust the pH value to 5-6, filter to obtain a lithium-containing ammonium sulfate solution, then perform MVR evaporation concentration at a concentration temperature of 110° C., centrifuge to separate the crystallized ammonium sulfate, obtain a saturated ammonium sulfate mother liquor with a pH value of 2-3 and a lithium content of 2000-5000 ppm, then add ammonia water or ammonium bicarbonate to adjust the pH to 5-7.5, filter to obtain calcium slag and magnesium slag, add ammonium bicarbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, and add ammonia water to adjust the pH value to 7.5-10, stir at a temperature of 95° C. for 1 hour, then keep warm and stand for 10 hours, filter to obtain a lithium carbonate filter cake, wash with water to remove the ammonium sulfate in the lithium carbonate, obtain an industrial-grade lithium carbonate wet cake, and dry to obtain industrial-grade lithium carbonate.
[0060] Embodiment 3:
[0061] A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag comprises the following steps:
[0062] (1) the iron-phosphorus slag raw material is subjected to a first acid leaching and dissolving with 6% sulfuric acid, wherein the raw material mass is dissolved by 60%, and a primary leaching solution and a primary leaching residue are obtained by filtration. The primary leaching residue is subjected to a second acid leaching with 50% sulfuric acid to completely dissolve the raw material, and a secondary leaching solution and a secondary leaching residue are obtained after filtration. The secondary leaching residue is carbon black; new iron-phosphorus slag raw material is added to the secondary leaching solution and an appropriate amount of low-concentration sulfuric acid is added to the acid leaching solution until the sulfuric acid concentration of the acid leaching solution is 6%, and a new primary leaching solution and a primary leaching residue are obtained; the first acid leaching temperature is 25° C.; the second acid leaching temperature is 25° C., the amount of sulfuric acid added in the first acid leaching accounts for 60% of the total amount of sulfuric acid in the two acid leachings, and the amount of sulfuric acid added in the second acid leaching accounts for 40% of the total amount of sulfuric acid in the two acid leachings;
[0063] (2) Controlling the speed of adding alkali to the new primary leaching solution, gradually add ammonia water to a concentration of 5%, and control the end point pH value to 1.0. Filter and wash to obtain filter cake 1 and tail liquid.
[0064] (3) After dissolving the filter cake 1 with an appropriate amount of sulfuric acid, ammonia water is gradually added again by controlling the speed of adding alkali, the concentration is 10%, and the end point pH value is controlled at 1.1, and the filter cake 2 is obtained by filtering and washing; acidic water is used for washing in the steps (2) and (3), and the pH value of the acidic water is 1.3;
[0065] (4) slurrying the filter cake 2 obtained in step (3) with pure water, adding phosphoric acid, adjusting the temperature to 90° C., keeping the temperature for 2 h, filtering to obtain the filter cake 3, washing with pure water until the conductivity is less than 500 μS / cm, the phosphoric acid concentration is 80%, and the pH value is controlled at 1.0;
[0066] (5) The filter cake 3 obtained in step (4) is dried and calcined to obtain anhydrous titanium-containing iron phosphate. The drying temperature is 100° C., the drying time is 6 h, and the calcination temperature is 530° C., and the time is 4 h.
[0067] Comparative Example 1:
[0068] The difference between Comparative Example 1 and Example 1 is that the iron phosphorus slag raw material used does not contain titanium components, and titanium is added during the synthesis of lithium iron phosphate.
[0069] Comparative Example 2:
[0070] The difference between Comparative Example 2 and Example 1 is that the iron-phosphorus slag raw material used does not contain titanium, and titanium is not added during the synthesis of iron phosphate and lithium iron phosphate.
[0071] The metal element content and performance index of the synthetic ferric phosphate obtained in the above Examples 1-3 were tested, and the test results are shown in the following table:
[0072] Table 4
[0073]
[0074]
[0075] The iron phosphate obtained in Example 1-3 and Comparative Example 1-2 is mixed with lithium carbonate and glucose in a stoichiometric ratio, with a molar ratio of iron phosphate to lithium carbonate of 2:1, and the amount of glucose added accounting for 7% of the mass of the raw material mixture. The mixture is mixed evenly, and lithium iron phosphate is obtained by wet grinding, drying, high-temperature sintering and grinding. The drying temperature is 100°C for 5 hours, and the high-temperature sintering temperature is 700°C for 10 hours. The performance experimental test results are shown in the following table.
[0076] Table 5
[0077]
[0078] It should be noted that, in this article, the terms: include, contain and any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used in this article to illustrate the principle and implementation of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements, modifications or changes can be made, and the above technical features can also be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag, characterized in that: The following steps are involved: (1) The iron-phosphorus slag raw material is subjected to a first acid leaching and dissolution with sulfuric acid of 5-10% by mass, and the raw material mass is dissolved by 50-80%, and the primary leaching solution and primary leaching residue are obtained by filtration. The primary leaching residue is subjected to a second acid leaching with sulfuric acid of 11-50% by mass to completely dissolve the iron phosphate therein, and the secondary leaching solution and secondary leaching residue are obtained after filtration, and the secondary leaching residue is carbon black; new iron-phosphorus slag raw material is added to the secondary leaching solution, and an appropriate amount of low-concentration sulfuric acid is added to the acid leaching solution until the sulfuric acid concentration of the acid leaching solution is 5-10%, and a new primary leaching solution and primary leaching residue are obtained; the chemical reaction equation involved in the above acid leaching is as follows: 2AlPO4+3H2SO4=Al2(SO4)3+2H3PO4 2FePO4+3H2SO4=Fe2(SO4)3+2H3PO4 Ti3(PO4)4+6H2SO4=3Ti(SO4)2+4H3PO4; (2) Alkali is gradually added to the new primary leaching solution, and the end point pH value is controlled at 1-1.
8. After filtering and washing, filter cake 1 and tail liquid are obtained. The chemical reaction equation involved in adjusting the pH value is as follows: <h2 style=";text-align:left;direction:ltr">H3PO4+3OH<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> =PO4<h2 style=";text-align:left;direction:ltr"> 3- <h2 style=";text-align:left;direction:ltr"> +3H2O Fe 3+ +PO4 3- +2H2O=FePO4·2H2O↓ 3Ti 4+ +4PO4 3- =Ti3(PO4)4↓; (3) After dissolving the filter cake 1 with sulfuric acid, alkali is gradually added again by controlling the speed of adding alkali, and the end point pH value is controlled at 1-1.8, and the filter cake 2 is obtained by filtering and washing; (4) slurrying the filter cake 2 obtained in step (3) with pure water, adding phosphoric acid, adjusting the temperature to 85-95° C., keeping the temperature for 2-3 hours, filtering to obtain the filter cake 3, and washing with pure water until the conductivity is less than 500 μS / cm; (5) Drying and calcining the filter cake 3 obtained in step (4) to obtain anhydrous titanium-containing iron phosphate.
2. A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag according to claim 1, characterized in that: In step (1), the temperature of the first acid leaching is 25-60°C; the temperature of the second acid leaching is 35-80°C, the amount of sulfuric acid added in the first acid leaching accounts for 50-80% of the total amount of sulfuric acid in the two acid leachings, and the amount of sulfuric acid added in the second acid leaching accounts for 20-50% of the total amount of sulfuric acid in the two acid leachings.
3. A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag according to claim 1, characterized in that: The tail liquid treatment method in step (2) is to recycle and utilize the tail liquid to prepare lithium carbonate. There are two specific recycling methods: one is that if the tail liquid is obtained after adding ammonia water to the new primary leachate to precipitate iron phosphate, then continue to add ammonia water to adjust the pH value to 5-6, filter to obtain a lithium-containing ammonium sulfate solution, and then perform MVR evaporation concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized ammonium sulfate to obtain a saturated ammonium sulfate mother liquor with a pH value of 2-3 and a lithium content of 1000-10000ppm, then add ammonia water or ammonium bicarbonate to adjust the pH to 5-7.5, filter to obtain calcium slag and magnesium slag, add ammonium bicarbonate to the filtrate in an amount of more than 1 times the molar number of lithium in the solution, and add ammonia water to adjust the pH value to 7.5-10, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, and wash with water to remove the lithium carbonate. ammonium sulfate is added to obtain industrial-grade lithium carbonate wet cake, which is then dried to obtain industrial-grade lithium carbonate. Another method is to add liquid alkali to the new primary leachate to precipitate iron phosphate to obtain the tail liquid, then continue to add liquid alkali or sodium carbonate to adjust the pH value to 6-7, filter to obtain a sodium sulfate solution containing lithium, and then perform MVR evaporation and concentration at a concentration temperature of 90-110°C, centrifuge and separate the crystallized sodium sulfate to obtain a saturated sodium sulfate mother liquor with a pH value of 6-7 and a lithium content of 1000-10000ppm, then add sodium carbonate to adjust the pH to 6-7.5, filter to obtain calcium slag and magnesium slag, add sodium carbonate to the filtrate in an amount of more than 1 times the molar number of lithium element in the solution, stir at a temperature of 70-95°C for 1-3h, then keep warm and stand for 1-24h, filter to obtain a lithium carbonate filter cake, wash with water to remove sodium carbonate in the lithium carbonate, obtain an industrial-grade lithium carbonate wet cake, and dry to obtain industrial-grade lithium carbonate.
4. A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag according to claim 1, characterized in that: In the steps (2) and (3), the alkali is selected from liquid alkali or aqueous ammonia, the mass concentration of the liquid alkali is 10-30%, and the mass concentration of the aqueous ammonia is 5-20%.
5. A process for preparing battery-grade iron phosphate by recycling iron-phosphorus slag according to claim 1, characterized in that: In the steps (2) and (3), acidic water is used for washing, and the pH value of the acidic water is 1-1.
5.
6. The process for preparing battery-grade iron phosphate and lithium iron phosphate by recycling iron phosphorus slag according to claim 1, characterized in that: In the step (4), the mass concentration of phosphoric acid is 75-85%, and the pH value is controlled at 0.8-2.
0.
7. The process for preparing battery-grade iron phosphate and lithium iron phosphate by recycling iron phosphorus slag according to claim 1, characterized in that: In the step (5), the drying temperature is 75-105° C. and the drying time is 2-10 h.
8. The process for preparing battery-grade iron phosphate and lithium iron phosphate by recycling iron-phosphorus slag according to claim 1, characterized in that: In the step (5), the calcination temperature is 500-600° C. and the calcination time is 3-5 hours.
9. A process for preparing lithium iron phosphate by recycling iron phosphorus slag, characterized in that: The iron phosphate prepared by the process described in any one of claims 1 to 7 is mixed with lithium carbonate and glucose in a stoichiometric ratio, and mixed evenly, and then wet-milled, dried, high-temperature sintered and ground to obtain lithium iron phosphate.
10. A process for preparing lithium iron phosphate by using recycled iron phosphorus slag according to claim 9, characterized in that: The molar ratio of iron phosphate to lithium carbonate is 2-3:1, and the amount of glucose added accounts for 6-8% of the mass of the raw material mixture; the drying temperature is 95-105°C, the time is 3-5h, and the high-temperature sintering temperature is 700-750°C, and the time is 9-10h.